Atlantic City - Frazier, Jason (East Carolina University, 2010)
Abstract  Atlantic City  by Jason Frazier  April, 2010  Director: Ron Mitchelson  DEPARTMENT OF ENGLISH  Atlantic City is a screenplay inspired in part by events that took place in Catskill, NY in  the early 1980's. The story follows Leon, a young fighter modeled after a teenage Mike Tyson,  who is plucked from a juvenile prison and trained to be a champion boxer. However, despite  Leon's considerable talent, he also has a dark side, which creates friction between his two  trainers, Teddy and Gus.  One of the primary themes of this story is integrity, which is a virtue espoused by both  Teddy and Gus. However, this principal is challenged by Leon whose potential offers  redemption, particularly for Gus, and a second chance at the glory that was taken away from him  in the opening scene. As Gus becomes seduced by Leon's talent, he ignores the growing signs of  trouble, and his relationship with Teddy begins to deteriorate. Teddy is well aware of the path  Leon is heading down and knows that without discipline, he will become a danger to himself and  others. He is also concerned with Gus' willingness to sell out his own ideals due to the prospect  of fame. Ultimately this conflict escalates to a level which threatens to alter the lives of all three  men.
Keywords: Performing arts; Fine arts; Boxing--Drama